Towards the development of a murabbi - Hussien, Suhailah (Universiti Putra Malaysia Press, 2009)
The aim of this chapter is to provide a critical analysis of the curriculum of Islamic education. The question to be addressed in this chapter is whether the current curriculum of Islamic education is able to realise the true purpose of Islamic education. In seeking the answer to this question, the chapter focuses on various views of curriculum and the different concepts of education they incorporate. To this end, the first section provides a conceptual framework for critically examining the curriculum, which draws on Habermas’ Theory of Knowledge-Constitutive Interests (KCI), and in particular, the way this is employed by Grundy (1987) to examine different kinds of curriculum policy, practice, and pedagogy. In the second section, the curriculum of Islamic education is analysed so as to identify its curriculum and the view of education it sustains. The next section suggests Kazmi’s (2003) personalised knowledge as an alternative view of Islamic education and how this view is able to realise the true purpose of Islamic education.